Evaluation of B cell related markers and autoantibodies in rheumatoid arthritis patients treated with abatacept - Wang, Ting; Giltiay, Natalia V.; Lood, Christian; Wang, Ning; Han, Bobby Kwanghoon (Frontiers in Immunology, 2025)
ObjectivesTo investigate whether biomarkers related to B cell activation and autoantibody production are associated with the response to abatacept in rheumatoid arthritis (RA) patients.MethodsTwenty-five patients with RA were enrolled in this study. Responders (n=10) to abatacept were subjects who achieved ACR50 response at week 24. Serum levels of soluble biomarkers were measured with ProcartaPlex by Luminex or ELISA. Peripheral blood mononuclear cells were isolated and analysed for T cell and B cell subsets by flow cytometry. Patients were genotyped for human leukocyte antigen (HLA)-DRB1 shared epitope (SE) alleles. Baseline levels and longitudinal changes of markers were assessed between responders and nonresponders.ResultsBaseline levels of anti-cyclic citrullinated peptide (anti-CCP) antibodies (p=0.01), IgM rheumatoid factor (RF) (p=0.02), CXC chemokine ligand 13 (CXCL13, p=0.02), sCD23 (p<0.05), as well as frequencies of CD19+CD11c+IgD-CD27- B cells (p=0.04), were higher in responders than nonresponders. Among them, anti-CCP and frequencies of CD19+CD11c+IgD-CD27- B cells were independently associated with response to abatacept. The presence of two alleles of SE was associated with responders (p=0.04). Patients with 2 alleles of SE had higher levels of anti-CCP (p=0.02) and IgM RF (p=0.04) compared to patients with 0 or 1 allele. Further, IgM RF and CXCL13 levels decreased only in responders (p=0.02 and 0.004 respectively, at week 24), while anti-CCP levels did not decrease significantly in either responders or nonresponders.ConclusionMarkers of B cell activation including anti-CCP and frequencies of CD19+CD11c+IgD-CD27- B cells in RA were associated with response to abatacept. IgM RF and CXCL13 decreased only in responders and could be potentially used as pharmacodynamic markers.